INFLUENCE OF WORK ENVIRONMENT AND EMPLOYEE COMPETENCE ANALYSIS ON EMPLOYEE PERFORMANCE - Hery Santoso, Muhammad; Naim, Sidrotun; Suroso, Suroso; Hayudini, Magna Anissa A.; Shrestha, Prabin (Chanos Chanos, 2023)
The research that has been done aims to analyze the effect of the work environment and employee competence on employee performance at a seafood processing company in Probolinggo City, East Java. Based on the results of the analysis of the calculation of the first hypothesis (H1), which states that the work environment has a positive and significant effect on employee performance, the t-count value of 19,845 is greater than the t-table value, which is 1,677 and the significance value obtained is less than 0.05, which means that the work environment has a positive and significant effect on employee performance, the results of the calculation analysis of the second hypothesis (H2) which states that employee competence has a positive and significant effect on employee performance obtained a t-count value of 14,471 greater than the t-table value of 1,677 and the value the significance obtained is less than 0.05, which means that employee competence has a positive and significant effect on employee performance, while the R-square value obtained is 0.897 which states that work environment variables and employee competency affect employee performance by 89.70% and the remaining 10.30% influenced by other variables.